"Does it change the nature of food and capitalism?" Exploring expert perspectives on public policies for a transition to 'less and better' meat and dairy. Issue 128 (February 2022) - Trewern, Joanna; Chenoweth, Jonathan; Christie, Ian
Abstract: To enable a transition to a more sustainable food future, it is crucial policymakers consider and address livestock production and meat consumption holistically. The concept of 'less and better' meat and dairy offers an alternative approach to industrial livestock production. This study explores perspectives of UK stakeholders engaged in political advocacy and implementation on policy priorities and specific policy measures aimed at facilitating a transition to 'less and better' meat in the UK. 16 UK experts on food and farming from the research, civil society, business and farming sectors were interviewed. Thematic analysis was conducted to identify convergence and divergence on views related to policy priorities and the potential for impact, political feasibility and unintended consequences of specific policy measures aimed at increasing the sustainability of livestock production or reducing meat consumption. Experts agreed on policy priorities but held divergent views on the potential for impact of specific policy measures. Economic structures including incentives, disincentives and food prices were highlighted as having the greatest influence over meat production and consumption practices. Highlights: Expert interviews investigated views on policies for reducing meat consumption and improving sustainability of production. Utilizing 'less and better' meat as a framework can support holistic policymaking on food and farming. Ultra-processed meat tax seen as highest impact measure to reduce meat consumption. Nitrogen targets and fiscal measures seen as needed to produce livestock more sustainably. Addressing both production and consumption is crucial to avoid unintended consequences.